TANGGUNG JAWAB KURIR PAKET ONLINESHOP DALAM TRANSAKSI COD TERHADAP PAKET DIRUSAK KONSUMEN DI KOTA PONTIANAK - NIM. A1011201247, BANGUN JAIMAN SILABAN (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACTThe existence of Law Number 11 of 2008 concerning the Implementation of Information Systems and Electronic Transactions indicates that technological developments, namely the internet, have become a necessity for society. The development of internet technology has included the realm of commerce which can be accessed through online shopping applications. Online shopping makes it easier for users to shop without going to the seller's location and making payments easy and safe, such as paying at the buyer's location as the recipient of the order (Cash On Delivery). The Cash On Delivery (COD) payment method is the most popular payment method among consumers in Indonesia. However, the COD method also has problems where quite a few couriers are the target of consumer disappointment due to incompatibility of goods in the package, the complexity of returning ordered goods and so on.The problem formulation in this research is: